Lanosterol Eye Drops in a Human Juvenile Nuclear Cataract - A, Felici; D, Mengato; M, Falciani; E, Bertelli (Archives of Clinical and Medical Case Reports, 2018)
A revolutionary non-surgical and low-cost treatment of the largest cause of world's blindness could have an immeasurable effect on global health, since surgical procedures are not accessible to all patients worldwide. In cataracts we still keep replacing a clouded lens without considering the pathogenetic mechanism of lens clouding, and without helping the lens epithelium to restore its homeostatic functions. In the light of recent scientific findings and considering the lack of studies on humans in this field we tested lanosterol eye drops on a human juvenile nuclear cataract with a lower lanosterol concentration and with a different vehicle compared to the eye drops recently tested on animals. Our experiment has demonstrated that there were no clinically relevant changes in intraocular pressure neither reversal of cataract using eye drops with a relatively low dose of lanosterol. These results encourage to test eye drops with higher lanosterol concentrations on human cataract cases.